(untitled) (Solukhumbu Multiple Campus Research Journal, 2024)
This study, "Transforming ELT with ICT: Empowerment or Encumbrance," investigates the impact of Information and Communication Technology (ICT) on English Language Teaching (ELT) in Nepalese secondary schools. The research integrates qualitative research design and semi-structured interviews to evaluate the practical integration of ICT. Participants include 3 secondary level English teachers from public schools in urban, semi-urban and rural areas of Nepal. The findings reveal that ICT significantly enhances student engagement and language proficiency through interactive tools and multimedia resources, contributing to more personalized learning experiences. However, challenges such as inadequate infrastructure, inconsistent internet access, and insufficient teacher training persist, creating disparities in technology access and impacting equitable benefits. Addressing these issues through improved infrastructure, targeted training, and equitable access strategies is crucial for optimizing ICT’s potential in ELT. The implication of the research highlights ICT’s potential to enhance student engagement and language proficiency in ELT but emphasizes the need for better infrastructure, consistent access, and teacher training to ensure equitable benefits for all learners.